2015
DOI: 10.22146/gamaijb.6147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self Service Technology Quality on Customer Satisfaction: A Case of Retail Banks in Western Province in Sri Lanka

Abstract: Rapid technological advancement in the banking environment drives Sri Lankan banks to adopt self-service technologies to deliver services via SMS banking, Internet banking and telephone banking facilities, Automated Teller Machines (ATM) etc. This study explored the perceived quality of the selfservice technology of these services and its effect on customer satisfaction. The literature survey and in depth interviews helped to formulate quality dimensions: security, efficiency, eases of use, reliability and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…However, two other SST usage factorssecurity and responsivenesswere not found to have a significant positive influence on customer satisfaction. These results are consistent with those reported by Gunawardana et al (2015) where security and time savings were not found to positively contribute to customer satisfaction. Furthermore, the failure to find a direct effect of security on customer satisfaction could have been due to customers' assumption that it is a fundamental responsibility for banks to ensure that their SST-based transactions are performed in a highly secure and confidential environment.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, two other SST usage factorssecurity and responsivenesswere not found to have a significant positive influence on customer satisfaction. These results are consistent with those reported by Gunawardana et al (2015) where security and time savings were not found to positively contribute to customer satisfaction. Furthermore, the failure to find a direct effect of security on customer satisfaction could have been due to customers' assumption that it is a fundamental responsibility for banks to ensure that their SST-based transactions are performed in a highly secure and confidential environment.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 92%
“…The chances of customers' using the ATM system will be higher if this system is easy to use and error-free, which will eventually lead to higher customer satisfaction (Narteh, 2015). Overall, reliability is an Contingent role of cashrecycling ATM-SST important dimension of SSTs' service quality and the strongest cause of satisfaction among users (Fernandes and Pedroso, 2017;Gunawardana et al, 2015). Therefore, based on the evidence briefly reviewed above, the first hypothesis to be tested in the present study can be formulated as follows:…”
Section: Reliabilitymentioning
confidence: 95%
“…Technology acceptance model and trust significantly influence customer satisfaction Juliana, Djakasaputra, Pramono & Hulu (2020) Ease of use, Trust, quality, brand image, price, customer satisfaction and purchase intention Ease of use, trust and quality and purchase intention have significant positive effects on customer satisfaction Hossain, Zhou & Rahman (2019) Features of customer satisfaction (speed, ease of use, reliability, enjoyment control) Speed, ease of use, reliability, enjoyment have control positive relationship with customer satisfaction Barua, Aimin & Hongyi (2017) Perceived reliability and customer satisfaction model Perceived reliability positively influence trust. Trust have significant influence on customer satisfaction Ghani, Rahi, Yasin & Alnaser (2017) Role of technology acceptance model with satisfaction Ease of use, customer service and usefulness influence customer satisfaction positively which further develop adoption attitude Robertson, McDonald, Leckie & McQuilken (2016) Antecedents (speed, ease of use, enjoyment, control, reliability) and consequences (trust, word of mouth, reuse Speed, ease of use, enjoyment, control and reliability have positive relation with customer satisfaction intention) of customer satisfaction Gunawardana, Kulathunga & Perera (2015) Service quality attributes Service quality attributes positively associated with customer satisfaction…”
Section: Resultsmentioning
confidence: 99%
“…Four items of PU and four items of PEOU were adapted from the original model Davis (1989). For additional variables, five items of perceived reliability adapted from Gunawardana and Perera (2015), Hossain et al (2019) and Peng et al (2016), three items of price value from UTAUT-2 (Venkatesh et al , 2012), four items of technology anxiety from Eisingerich and Bell (2008), four items of behavioral intention from Venkatesh et al (2012) and five items of actual use behavior were adapted from Taylor and Todd (1995). To ensure that the instrument better fit this empirical study, some minor changes were made to ensure easy interpretation and comprehension of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of health-care services, reliability is the most important factor in selecting the health services because of lifetime consequences for improper treatment. Reliability, a fundamental attribute of superior service quality (Gunawardana and Perera, 2015), is characterized by an SST's perfect technical functioning to deliver the service accurately (Elliott et al, 2013). In addition to this, Skard and Nysveen (2016) stated that if customers perceived the systems as easy to use they will perceive the systems as reliable and trustworthy.…”
Section: Perceived Reliabilitymentioning
confidence: 99%